PERSEPSI DALAM TRANSFORMASI KARYA SASTRA : STUDI PENGGUNAAN PUISI BUNGA DAN TEMBOK OLEH KELOMPOK MUSIK MERAH BERCERITA - Fitriyanto, Choiri (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2018)
ABSTRACTÂ This paper attempts to describe how the Merah Bercerita music group builds the perception of Wiji Thukul's poem entitled "Flower and Wall" and pours it into a song. It is noteworthy that this musical work is not merely showing the phenomenon of mere musical performances, but also is an effort in giving musical power to the poetic text that is full of social criticism. In this qualitative research, data collection is done with emphasis on the concept of perception as the main perspective, then the data is interpreted to be analysed. The conclusion of this research is the existence of three stages in the process of perception conducted by Merah Bercerita group, namely (1) sensation, (2) attention, and (3) interpretation.Â Kata Kunci : persepsi, puisi, musik, bentuk musik